Flickr hypergroups - Negoescu, R.; Adams, Brett; Phung, Dinh; Venkatesh, Svetha; Gatica-Perez, D. (ACM, 2009)
The amount of multimedia content available online constantly increases, and this leads to problems for users who search for content or similar communities. Users in Flickr often self-organize in user communities through Flickr Groups. These groups are particularly interesting as they are a natural instantiation of the content + relations social media paradigm. We propose a novel approach to group searching through hypergroup discovery. Starting from roughly 11,000 Flickr groups' content and membership information, we create three different bag-of-word representations for groups, on which we learn probabilistic topic models. Finally, we cast the hypergroup discovery as a clustering problem that is solved via probabilistic affinity propagation. We show that hypergroups so found are generally consistent and canbe described through topic-based and similarity-based measures. Our proposed solution could be relatively easily implemented as an application to enrich Flickr's traditional group search.